2012
DOI: 10.5897/ajmr12.151
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of informally marketed bovine milk with Staphylococcus aureus in urban and peri urban areas of Debre-Zeit, Ethiopia

Abstract: A cross-sectional study was conducted from October, 2009 to March, 2010 to assess the level of contamination of informally marketed milk with Staphylococcus aureus at farms and milk collection centers in Debre-Zeit, Ethiopia. One hundred and seventy raw farm bulk milk samples, 25 mixed bulk milk samples and 20 pasteurized and packaged milk samples were collected from 14 milk collection centers and isolation and identification of S. aureus were carried out following standard method. S. aureus was isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
4
3
0
Order By: Relevance
“…This pattern is likely influenced by the extensive use of oxytetracycline, the predominant antibiotic for treating animal bacterial infections in Ethiopia [ 73 ]. Our findings are consistent with previous studies documenting tetracycline resistance rates ranging from 32.4 to 47.8% in milk and milk products in Ethiopia [ 11 , 53 , 70 ], Algeria [ 2 ], Egypt [ 46 ], and China [ 5 ]. Contrary to our results, earlier studies in Ethiopia [ 22 , 48 ], Iran [ 9 ], and Uganda [ 54 ] reported a high proportion of tetracycline-resistant S. aureus strains, ranging from 56.1 to 83.33%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This pattern is likely influenced by the extensive use of oxytetracycline, the predominant antibiotic for treating animal bacterial infections in Ethiopia [ 73 ]. Our findings are consistent with previous studies documenting tetracycline resistance rates ranging from 32.4 to 47.8% in milk and milk products in Ethiopia [ 11 , 53 , 70 ], Algeria [ 2 ], Egypt [ 46 ], and China [ 5 ]. Contrary to our results, earlier studies in Ethiopia [ 22 , 48 ], Iran [ 9 ], and Uganda [ 54 ] reported a high proportion of tetracycline-resistant S. aureus strains, ranging from 56.1 to 83.33%.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, in agreement with the present study, prevalence of 41.1% and 53% were reported in retail markets in Egypt [ 44 ] and bulk cooling tanks in Portugal, respectively. On the other hand, higher contamination rates of 80% and 72% were observed in MCCs in Sebeta [ 22 ] and Debre-Zeit [ 46 ] in Ethiopia, respectively, and 61.7% in retail raw milk samples in China [ 47 ]. In contrast, earlier investigations reported lower contamination rates, including 23.08% in Holeta at collection centers [ 11 ], 17.5% in Ambo and Bako towns in bulk tank milk at farm level [ 48 ] in Ethiopia, and 15.7% in raw cow milk in Iran [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study showed that the occurrence of S. aureus in bulk milk (42%) was high compared to previous reports from other parts of Ethiopia [26,28,54,74], Uganda [75], Brazil [76], the USA [17] and China [77]. Our finding complies with previous reports from Ethiopia [27], Greece [70] and Italy [78]. In contrast, slightly higher S. aureus-occurrences of 66, 61, 54, 51, 48% were reported in Brazil [15], India [58], Portugal [73], Ireland [49] and the USA [79], respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Staphylococcus aureus is a major cause of bovine mastitis [20], resulting in large economic losses due to reduced milk production and quality [21]. S. aureus is frequently isolated from cows with mastitis [22][23][24][25] and bulk milk [26][27][28] in Ethiopia. The presence of S. aureus in bulk milk samples indicates that infected cows are present in a herd [9].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Consumption of raw milk and its products such as cheese, cream, and yogurt is common in sub-Saharan Africa, including Ethiopia. 16,17 However, the production and consumption of raw milk and various dairy products often takes place under poor hygiene conditions. 16,18 However, still there is a limited evidence on the prevalence of S. aureus in camel milk and determinant factors in Ethiopia, which cover both production and market areas.…”
Section: Introductionmentioning
confidence: 99%